2016
DOI: 10.1111/mec.13742
|View full text |Cite
|
Sign up to set email alerts
|

The mutational hazard hypothesis of organelle genome evolution: 10 years on

Abstract: Why is there such a large variation in size and noncoding DNA content among organelle genomes? One explanation is that this genomic variation results from differences in the rates of organelle mutation and random genetic drift, as opposed to being the direct product of natural selection. Along these lines, the mutational hazard hypothesis (MHH) holds that 'excess' DNA is a mutational liability (because it increases the potential for harmful mutations) and, thus, has a greater tendency to accumulate in an organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 56 publications
4
53
0
Order By: Relevance
“…2012). Although a handful of exceptions have been noted, the effect of random genetic drift and mutation rates gives an alternative explanation for organelle genomic evolution (Smith 2016). …”
Section: Introductionmentioning
confidence: 99%
“…2012). Although a handful of exceptions have been noted, the effect of random genetic drift and mutation rates gives an alternative explanation for organelle genomic evolution (Smith 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shown that 5' splicing signal, the polypyrimidine tract and 3' splicing signal of introns from left to right. We found that the consensus signals of the introns of the carnivorous plants were similar to those of eukaryotes, like land plants, metazoan and mammals (Irimia and Roy, 2008;Ma et al, 2015a;2016).…”
Section: Intron Consensus Sequence In the Carnivorous Plantsmentioning
confidence: 73%
“…By comparing the nuclear genomes and organellar genomes, Lynch found a large number of introns accumulation in the nuclear genome and he believes that it is due to differences in the mutation rates between the two genomic groups. Meanwhile, he also found that the complexity of the organelle genome was significantly reduced, supporting the mutationalhazard hypothesis Smith, 2016).…”
Section: Introductionmentioning
confidence: 73%
“…The roots of organelle genomic expansion are complicated and multifaceted (Smith, 2016). There is increasing evidence that DNA maintenance machineries play a key role in organelle genomic architecture, including genome size (Smith and Keeling, 2015).…”
Section: Ptdna-coding Capacity Is Highly Conserved Among Colorless Algaementioning
confidence: 99%